Prevalence And Determinants of Vaginal Discharge Among Women of Reproductive Age Group in Tertiary Care Hospital of Northern India - Varsha Chaudhary; Rajeev Kumar; Vijender K Agrawal; Arun Singh; Ramesh Narula; Mahendra Sharma (Medsci Publications, 2012)
Background: The complaint of vaginal discharge is very common, particularly in south East Asia it is associated with considerable disability, health seeking, and associated costs. Objective: To estimate the hospital based prevalence of vaginal discharge, to find out socio-demographic variables associated with the complaint of vaginal discharge, perceived causes of vaginal discharge and association of vaginal discharge with other gynaecological problems among the women of reproductive age. Methods: The present cross sectional study was conducted in one of the tertiary care hospital of Bareilly district. The respondent were the female in reproductive age group (15-49yrs) attending Obst. & gynae OPD. Sample size of 590 was calculated, for sample to be more representative of population, a total of 1100 female in reproductive age group were included in the study. . Odds ratio (OR) and their 95% confidence interval (CI) were calculated to estimate the strength of association between vaginal discharge and other gynaecological symptoms. Chi square test was applied as test of significance for data analysis. Results: Prevalence of vaginal discharge was found to be 24.6%. Factors like increasing age, married (26.2%), illiteracy (60.1%), Muslim religion (28.7%), low socioeconomic status, high parity, history of induced abortion and place of delivery were found to be significantly associated with vaginal discharge. Internal gynaecological problem was perceived as a main cause for vaginal discharge (73.3%). Vaginal discharge was found to be significantly associated with other gynaecological problems. Recommendation: There is need for creating community awareness about health care facilities and